Do Board Characteristics Impact Green Banking Disclosure? Empirical Evidence from Indonesia - Dessy Noor Farida; Agus Purwanto (Indonesian Journal of Sustainability Accounting and Management, 2021)
In performing their role in implementing the United Nations Sustainability Development Goals (SDGs), banks have started to run their businesses in a more environmentally friendly manner through green banking activities. implementing green banking activities requires good corporate governance. This study, therefore, examines the effects of 1) board size, 2) an independent board of commissioners, and 3) institutional ownership on the disclosure of green banking in sharia banks in Indonesia. This research is quantitative. The sample includes all the 13 commercial sharia banks in Indonesia. The data analysis technique used a multiple linear regression test. The findings indicate that board size positively affects green banking disclosure, while institutional ownership and an independent board of commissioners do not appear to influence green banking disclosure at all. The control variable that affects the disclosure of green banking the most is company size. Therefore, this study recommends that the sharia banking sector increase green banking disclosures for stakeholders because such disclosure by companies desiring to express banking concerns about social and environmental aspects can increase corporate value.